Model Manajemen Keuangan Syariah Di Pesantren: Meningkatkan Kemandirian Ekonomi Lembaga Pendidikan Islam di Era Digital - Misbah, Ahmad (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2024)
Digital-based financial management models have become an urgent need for Islamic boarding schools to improve the efficiency, transparency, and accountability of fund management. Islamic boarding schools, as Islamic-based educational institutions, often face challenges such as dependence on external funding, limited skilled human resources, and inadequate digital infrastructure. This study aims to identify and analyze a digital-based financial management model that is in accordance with sharia principles to strengthen the economic independence of Islamic boarding schools in the digital era. This study uses a library research approach to collect data from various scientific literature related to Islamic financial management, digitalization, and management of Islamic educational institutions. Data analysis was carried out descriptively to identify challenges and opportunities for the implementation of sharia-based digital financial systems in Islamic boarding schools. Descriptive analysis is carried out to understand existing concepts and models. Critical analysis is used to evaluate the relevance and suitability of literature to the context of Islamic boarding schools in Indonesia. The results of the study show a reduction in administrative costs, an increase in operational efficiency, and higher public trust in the management of pesantren funds. By combining digital technology and sharia principles, pesantren can reduce their dependence on external donations and ensure their financial sustainability in the digital era. These findings contribute to the literature on sharia-based financial management as well as provide practical guidance for Islamic boarding schools to implement a modern and sharia-compliant financial system.